Evaluation of white blood cell count as a possible prognostic marker for oral cancer - Kruse, Astrid L (BioMed Central, 2011)
INTRODUCTION: There seems to be increasing evidence that inflammation leads to cancer. For several cancers, an association with white blood cell (WBC) count has been reported. So far, no studies have been performed for cancer of the oral cavity and WBC. Therefore, the aim of the present study was to look at whether WBC count can be used as a prognostic marker for recurrence or metastases for oral cancer. MATERIAL AND METHODS: For 278 patients with oral cancer, the preoperative WBC count was compared with the clinicopathological information: age, gender, T-status, N-status, recurrence, metastases, follow-up time, and time till recurrence or metastases appeared. RESULTS: Out of 278 patients, 48 developed recurrence, 24 second tumors, 46 cervical metastases, and 14 distant metastases. The mean follow-up time was 35.97 months (range: 12-107 months). Significant Pearson correlation at the 0.05 level could be found for the T-status (0.046), but not for the N status (0.121). No significant correlation could be found between WBC count and the development of recurrence or metastases. CONCLUSION: In conclusion, our findings demonstrate that elevated WBC count does not seem to be a predictor for recurrence or for further metastases. Further research is recommended to investigate the WBC count in precancerous lesions and in HPV positive patients with oral SCC.